A characterization of local spatio-temporal variability in daytime occurrence of fog along the Oregon coast using public cameras and airport weather metrics - Sonya Rauschenbach; John B. Kim; Alex W. Dye; Ian Faloona; R. Cotton Rockwood; Christopher J. Still; Kyaw Tha Paw U; Adele L. Igel (Agricultural and Forest Meteorology, 2026)

Atmospheric Boundary Layer Control on Forest Thermal Properties - Matteo Detto; Christopher Still; Amilcare Porporato (Global Change Biology, 2026)
Forest canopy, air temperatures and air humidity (, , and ) play a central rol in regulating energy and gas exchange between vegetation and the atmosphere. Although often treated as independent drivers of canopy processes, and are dynamically coupled to via surface energy fluxes and atmospheric boundary layer (ABL) development. We investigated how plant physiology mediates this coupling. Using data from a tropical ecosystem, we studied a process‐based forest model dynamically coupled with an ABL growth model to simulate diurnal interactions between the canopy and the atmosphere. We systematically varied plant traits related to water use and thermal regulation to assess their effects on coupling and feedback. We focused on three metrics: the slope of the relationship, the peak of reached during the day and the lag between the maximum and , indicating hysteresis. Conservative water use, by reducing transpiration, leads to greater canopy warming, which intensifies sensible heat flux and accelerates ABL growth. This, in turn, raises near‐surface air temperature and vapor pressure deficit (VPD), amplifying thermal and water stress. In contrast, greater water use enhances evaporative cooling and slows ABL development, thereby moderating these feedback. Surprisingly, the slope of the relationship is quite insensitive to plant water‐use syndromes. This insight extends beyond modeling. Empirical studies often treat and VPD as independent drivers of transpiration, photosynthesis, or stomatal conductance. Our results challenge this assumption, showing that these variables are influenced by plant function itself. is not a passive outcome but an active mediator of energy, water, and carbon exchange, regulated by a feedback loop involving leaf physiology and atmospheric dynamics. Studies using or the relationship—whether from remote sensing or field data—as a proxy for forest stress or function, must account for this coupling.

Extreme Heatwave Causes Immediate, Widespread Mortality of Forest Canopy Foliage, Highlighting Modes of Forest Sensitivity to Extreme Heat - Adam Sibley; Christopher Still; Matthew Gregory; Constance Harrington; David Shaw; Nina Ferrari; Alex Dye; Mark Schulze; Glenn Howe; David E. Rupp; Christopher Daly; Daniel DePinte; et al. (Global Change Biology, 2025)
In late June 2021, multiple days of record‐breaking heat caused an unprecedented amount of foliage death in the forests of the Pacific Northwest, USA. Portions of tree canopies with healthy green foliage prior to the heat changed to red or orange shortly after the event. The change in foliage color could be readily seen in satellite imagery and was corroborated as foliar death (heat scorch) by aerial surveys and extensive observations on the ground. To better understand the patterns and processes driving foliar death, we used satellite imagery to identify 293,546 ha of forest, or ~4.7% of forest area, that were damaged in western Oregon and Washington by this extreme heat event. Analysis of underlying drivers of the observed heat damage indicated greater sensitivity was related to abiotic factors such as sun exposure, aspect, and microclimate, as well as biotic factors like tree species and stand age, budburst phenology, and foliar pathogens impacting tree health. Iconic, culturally and economically significant species like western redcedar, western hemlock, and Sitka spruce were disproportionately sensitive to heat damage, including in old‐growth stands where they are canopy dominants. These findings highlight the multifaceted challenges posed to forests by extreme heat waves, and the need to better understand their impact on forest ecosystems in a rapidly warming climate.

Network of networks: Time series clustering of AmeriFlux sites - David E Reed; Housen Chu; Brad G. Peter; Jiquan Chen; Michael Abraha; Brian Amiro; Ray G. Anderson; M. Altaf Arain; Paulo Arruda; Greg A. Barron-Gafford; Carl Bernacchi; Daniel P. Beverly; et al. (Agricultural and Forest Meteorology, 2025)

Overstory and understory leaves warm faster than air in evergreen needleleaf forests - Keenan Ganz; Christopher J. Still; Bharat Rastogi; L. Monika Moskal (Agricultural and Forest Meteorology, 2025)

Plant canopies exhibit stronger thermoregulation capability at the seasonal than diurnal timescales - Zhengfei Guo; Kun Zhang; Hua Lin; Bartosz M. Majcher; Calvin K.F. Lee; Christopher J. Still; Jin Wu (Agricultural and Forest Meteorology, 2023)

Evapotranspiration regulates leaf temperature and respiration in dryland vegetation - Christopher L. Kibler; Anna T. Trugman; Dar A. Roberts; Christopher J. Still; Russell L. Scott; Kelly K. Caylor; John C. Stella; Michael Bliss Singer (Agricultural and Forest Meteorology, 2023)

Convection-permitting climate simulations for South America with the Met Office Unified Model - Kate Halladay; Ron Kahana; Ben Johnson; Christopher Still; Giorgia Fosser; Lincoln Alves (Climate Dynamics, 2023)
We present the first convection-permitting regional climate model (CPRCM) simulations at 4.5 km horizontal resolution for South America at near-continental scale, including full details of the experimental setup and results from the reanalysis-driven hindcast and climate model-driven present-day simulations. We use a range of satellite and ground-based observations to evaluate the CPRCM simulations covering the period 1998–2007 comparing the CPRCM output with lower resolution regional and global climate model configurations for key regions of Brazil. We find that using the convection-permitting model at high resolution leads to large improvements in the representation of precipitation, specifically in simulating its diurnal cycle, frequency, and sub-daily intensity distribution (i.e. the proportion of heavy and light precipitation). We tentatively conclude that there are also improvements in the spatial structure of precipitation. We see higher precipitation intensity and extremes over Amazonia in the CPRCMs compared with observations, though more sub-daily observational data from meteorological stations are required to conclusively determine whether the CPRCMs add value in this regard. For annual mean precipitation and mean, maximum and minimum near surface temperatures, it is not clear that the CPRCMs add value compared with coarser-resolution models with parameterised convection. We also find large changes in the contribution to evapotranspiration from canopy evaporation compared to soil evaporation and transpiration compared with the RCM. This is likely to be related to the shift in precipitation intensity distribution of the CPRCMs compared to the RCM and its impact on the hydrological requires further investigation.

Networking the forest infrastructure towards near real-time monitoring – A white paper - Roman Zweifel; Christoforos Pappas; Richard L. Peters; Flurin Babst; Daniel Balanzategui; David Basler; Ana Bastos; Mirela Beloiu; Nina Buchmann; Arun K. Bose; Sabine Braun; Alexander Damm; et al. (Science of The Total Environment, 2023)

Representing plant diversity in land models: An evolutionary approach to make “Functional Types” more functional - Leander D. L. Anderegg; Daniel M. Griffith; Jeannine Cavender‐Bares; William J. Riley; Joseph A. Berry; Todd E. Dawson; Christopher J. Still (Global Change Biology, 2022)
Plants are critical mediators of terrestrial mass and energy fluxes, and their structural and functional traits have profound impacts on local and global climate, biogeochemistry, biodiversity, and hydrology. Yet, Earth System Models (ESMs), our most powerful tools for predicting the effects of humans on the coupled biosphere–atmosphere system, simplify the incredible diversity of land plants into a handful of coarse categories of “Plant Functional Types” (PFTs) that often fail to capture ecological dynamics such as biome distributions. The inclusion of more realistic functional diversity is a recognized goal for ESMs, yet there is currently no consistent, widely accepted way to add diversity to models, that is, to determine what new PFTs to add and with what data to constrain their parameters. We review approaches to representing plant diversity in ESMs and draw on recent ecological and evolutionary findings to present an evolution‐based functional type approach for further disaggregating functional diversity. Specifically, the prevalence of niche conservatism, or the tendency of closely related taxa to retain similar ecological and functional attributes through evolutionary time, reveals that evolutionary relatedness is a powerful framework for summarizing functional similarities and differences among plant types. We advocate that Plant Functional Types based on dominant evolutionary lineages (“Lineage Functional Types”) will provide an ecologically defensible, tractable, and scalable framework for representing plant diversity in next‐generation ESMs, with the potential to improve parameterization, process representation, and model benchmarking. We highlight how the importance of evolutionary history for plant function can unify the work of disparate fields to improve predictive modeling of the Earth system.

Changes in tree drought sensitivity provided early warning signals to the California drought and forest mortality event - Rachel M. Keen; Steven L. Voelker; S.‐Y. Simon Wang; Barbara J. Bentz; Michael L. Goulden; Cody R. Dangerfield; Charlotte C. Reed; Sharon M. Hood; Adam Z. Csank; Todd E. Dawson; Andrew G. Merschel; Christopher J. Still (Global Change Biology, 2022)
Climate warming in recent decades has negatively impacted forest health in the western United States. Here, we report on potential early warning signals (EWS) for drought‐related mortality derived from measurements of tree‐ring growth (ring width index; RWI) and carbon isotope discrimination (∆ 13 C), primarily focused on ponderosa pine ( Pinus ponderosa ). Sampling was conducted in the southern Sierra Nevada Mountains, near the epicenter of drought severity and mortality associated with the 2012–2015 California drought and concurrent outbreak of western pine beetle ( Dendroctonus brevicomis ). At this site, we found that widespread mortality was presaged by five decades of increasing sensitivity (i.e., increased explained variation) of both tree growth and ∆ 13 C to Palmer Drought Severity Index (PDSI). We hypothesized that increasing sensitivity of tree growth and ∆ 13 C to hydroclimate constitute EWS that indicate an increased likelihood of widespread forest mortality caused by direct and indirect effects of drought. We then tested these EWS in additional ponderosa pine‐dominated forests that experienced varying mortality rates associated with the same California drought event. In general, drier sites showed increasing sensitivity of RWI to PDSI over the last century, as well as higher mortality following the California drought event compared to wetter sites. Two sites displayed evidence that thinning or fire events that reduced stand basal area effectively reversed the trend of increasing hydroclimate sensitivity. These comparisons indicate that reducing competition for soil water and/or decreasing bark beetle host tree density via forest management—particularly in drier regions—may buffer these forests against drought stress and associated mortality risk. EWS such as these could provide land managers more time to mitigate the extent or severity of forest mortality in advance of droughts. Substantial efforts at deploying additional dendrochronological research in concert with remote sensing and forest modeling will aid in forecasting of forest responses to continued climate warming.

Poor relationships between NEON Airborne Observation Platform data and field‐based vegetation traits at a mesic grassland - Stephanie Pau; Jesse B. Nippert; Ryan Slapikas; Daniel Griffith; Seton Bachle; Brent R. Helliker; Rory C. O’Connor; William J. Riley; Christopher J. Still; Marissa Zaricor (Ecology, 2022)
Understanding spatial and temporal variation in plant traits is needed to accurately predict how communities and ecosystems will respond to global change. The National Ecological Observatory Network’s (NEON’s) Airborne Observation Platform (AOP) provides hyperspectral images and associated data products at numerous field sites at 1 m spatial resolution, potentially allowing high‐resolution trait mapping. We tested the accuracy of readily available data products of NEON’s AOP, such as Leaf Area Index (LAI), Total Biomass, Ecosystem Structure (Canopy height model [CHM]), and Canopy Nitrogen, by comparing them to spatially extensive field measurements from a mesic tallgrass prairie. Correlations with AOP data products exhibited generally weak or no relationships with corresponding field measurements. The strongest relationships were between AOP LAI and ground‐measured LAI ( r = 0.32) and AOP Total Biomass and ground‐measured biomass ( r = 0.23). We also examined how well the full reflectance spectra (380–2,500 nm), as opposed to derived products, could predict vegetation traits using partial least‐squares regression (PLSR) models. Among all the eight traits examined, only Nitrogen had a validation of more than 0.25. For all vegetation traits, validation ranged from 0.08 to 0.29 and the range of the root mean square error of prediction (RMSEP) was 14–64%. Our results suggest that currently available AOP‐derived data products should not be used without extensive ground‐based validation. Relationships using the full reflectance spectra may be more promising, although careful consideration of field and AOP data mismatches in space and/or time, biases in field‐based measurements or AOP algorithms, and model uncertainty are needed. Finally, grassland sites may be especially challenging for airborne spectroscopy because of their high species diversity within a small area, mixed functional types of plant communities, and heterogeneous mosaics of disturbance and resource availability. Remote sensing observations are one of the most promising approaches to understanding ecological patterns across space and time. But the opportunity to engage a diverse community of NEON data users will depend on establishing rigorous links with in‐situ field measurements across a diversity of sites.

Investigating old‐growth ponderosa pine physiology using tree‐rings, δ 13 C, δ 18 O, and a process‐based model - Danielle E. M. Ulrich; Christopher Still; J. Renée Brooks; Youngil Kim; Frederick C. Meinzer (Ecology, 2019)
In dealing with predicted changes in environmental conditions outside those experienced today, forest managers and researchers rely on process‐based models to inform physiological processes and predict future forest growth responses. The carbon and oxygen isotope ratios of tree‐ring cellulose (δ 13 C cell , δ 18 O cell ) reveal long‐term, integrated physiological responses to environmental conditions. We incorporated a submodel of δ 18 O cell into the widely used Physiological Principles in Predicting Growth (3‐ PG ) model for the first time, to complement a recently added δ 13 C cell submodel. We parameterized the model using previously reported stand characteristics and long‐term trajectories of tree‐ring growth, δ 13 C cell , and δ 18 O cell collected from the Metolius AmeriFlux site in central Oregon (upland trees). We then applied the parameterized model to a nearby set of riparian trees to investigate the physiological drivers of differences in observed basal area increment ( BAI ) and δ 13 C cell trajectories between upland and riparian trees. The model showed that greater available soil water and maximum canopy conductance likely explain the greater observed BAI and lower δ 13 C cell of riparian trees. Unexpectedly, both observed and simulated δ 18 O cell trajectories did not differ between the upland and riparian trees, likely due to similar δ 18 O of source water isotope composition. The δ 18 O cell submodel with a Peclet effect improved model estimates of δ 18 O cell because its calculation utilizes 3‐ PG growth and allocation processes. Because simulated stand‐level transpiration ( E ) is used in the δ 18 O submodel, aspects of leaf‐level anatomy such as the effective path length for transport of water from the xylem to the sites of evaporation could be estimated.

Fire deficits have increased drought sensitivity in dry conifer forests: Fire frequency and tree‐ring carbon isotope evidence from Central Oregon - Steven L. Voelker; Andrew G. Merschel; Frederick C. Meinzer; Danielle E. M. Ulrich; Thomas A. Spies; Christopher J. Still (Global Change Biology, 2019)
A century of fire suppression across the Western United States has led to more crowded forests and increased competition for resources. Studies of forest thinning or stand conditions after mortality events have provided indirect evidence for how competition can promote drought stress and predispose forests to severe fire and/or bark beetle outbreaks. Here, we demonstrate linkages between fire deficits and increasing drought stress through analyses of annually resolved tree‐ring growth, fire scars, and carbon isotope discrimination (Δ 13 C) across a dry mixed‐conifer forest landscape. Fire deficits across the study area have increased the sensitivity of leaf gas exchange to drought stress over the past >100 years. Since 1910, stand basal area in these forests has more than doubled and fire‐return intervals have increased from 25 to 140 years. Meanwhile, the portion of interannual variation in tree‐ring Δ 13 C explained by the Palmer Drought Severity Index has more than doubled in ca . 300–500‐year‐old Pinus ponderosa as well as in fire‐intolerant, ca . 90–190‐year‐old Abies grandis . Drought stress has increased in stands with a basal area of ≥25 m 2 /ha in 1910, as indicated by negative temporal Δ 13 C trends, whereas stands with basal area ≤25 m 2 /ha in 1910, due to frequent or intense wildfire activity in decades beforehand, were initially buffered from increased drought stress and have benefited more from rising ambient carbon dioxide concentrations, [CO 2 ], as demonstrated by positive temporal Δ 13 C trends. Furthermore, the average Δ 13 C response across all P. ponderosa since 1830 indicates that photosynthetic assimilation rates and stomatal conductance have been reduced by ~10% and ~20%, respectively, compared to expected trends due to increasing [CO 2 ]. Although disturbance legacies contribute to local‐scale intensity of drought stress, fire deficits have reduced drought resistance of mixed‐conifer forests and made them more susceptible to challenges by pests and pathogens and other disturbances.

Assessing earth system model predictions of C 4 grass cover in North America: From the glacial era to the end of this century - Christopher J. Still; Jennifer M. Cotton; Daniel M. Griffith (Global Ecology and Biogeography, 2019)
Aim C 4 grasses are distinct from C 3 grasses, because C 4 grasses respond in a different manner to light, temperature, CO 2 and nitrogen and often have higher resource‐use efficiencies. C 3 and C 4 grasses are typically represented in earth system models (ESMs) by different plant functional types (PFTs). The ability of ESMs to capture C 4 grass biogeography and ecology across differing time periods is important to assess, given the crucial role they play in ecosystems and their divergent responses to global change. Location North America. Time periods Last Glacial Maximum (LGM), historical modern period ( ca . 1850) and end of this century. Major taxa studied C 4 grasses. Methods Proxy data representing relative cover and productivity of C 4 grasses were collated, including carbon isotope ratios of soil carbon and animal grazer tissue, and vegetation plot data in undisturbed grasslands. We selected available model predictions of C 4 PFT percentage cover. Models were compared against one another and assessed against proxy data at key time points: the LGM, the historical modern period before widespread grassland conversion to agriculture, and the end of this century. Results We highlight large differences among model predictions of percentage C 4 grass cover across North America: all pairwise combinations have correlations 4 grass cover from proxy data, during either the LGM or the historical modern period. Models generally under‐predict percentage C 4 grass cover, particularly during the historical modern period. Main conclusions Earth system models do not accurately represent the biogeography of C 4 grasses across a range of time‐scales, and their outputs do not agree with one another. We suggest model improvements to represent this crucial functional type better, including more collection and greater integration of C 3 and C 4 grass trait data, explicit representations of tree–grass competition for water, and a greater focus on disturbance ecology.

Multi‐century stasis in C 3 and C 4 grass distributions across the contiguous United States since the industrial revolution - Daniel M. Griffith; Jennifer M. Cotton; Rebecca L. Powell; Nathan D. Sheldon; Christopher J. Still (Journal of Biogeography, 2017)
Aims Understanding the functional response of ecosystems to past global change is crucial to predicting performance in future environments. One sensitive and functionally significant attribute of grassland ecosystems is the percentage of species that use the C 4 versus C 3 photosynthetic pathway. Grasses using C 3 and C 4 pathways are expected to have different responses to many aspects of anthropogenic environmental change that have followed the industrial revolution, including increases in temperature and atmospheric CO 2 , changes to land management and fire regimes, precipitation seasonality, and nitrogen deposition. In spite of dramatic environmental changes over the past 300 years, it is unknown if the C 4 grass percentage in grasslands has shifted. Location Contiguous United States of America. Methods Here, we used stable carbon isotope data (i.e. δ 13 C) from 30 years of soil samples, as well as herbivore tissues that date to 1739 CE , to reconstruct coarse‐grain C 3 and C 4 grass composition in North American grassland sites to compare with modern vegetation. We spatially resampled these three datasets to a shared 100‐km grid, allowing comparison of δ 13 C values at a resolution and extent common for climate model outputs and biogeographical studies. Results At this spatial grain, the bison tissue proxy was superior to the soil proxy because the soils reflect integration of local carbon inputs, whereas bison sample vegetation across landscapes. Bison isotope values indicate that historical grassland photosynthetic‐type composition was similar to modern vegetation. Main conclusions Despite major environmental change, comparing modern plot vegetation data to three centuries of bison δ 13 C data revealed that the biogeographical distribution of C 3 and C 4 grasses has not changed significantly since the 1700s. This is particularly surprising given the expected CO 2 fertilization of C 3 grasses. Our findings highlight the critical importance of capturing the full range of physiological, ecological and demographical processes in biosphere models predicting future climates and ecosystems.

Leaf age and methodology impact assessments of thermotolerance of Coffea arabica - Danielle E. Marias; Frederick C. Meinzer; Christopher Still (Trees, 2017)

Coastal fog during summer drought improves the water status of sapling trees more than adult trees in a California pine forest - Sara A. Baguskas; Christopher J. Still; Douglas T. Fischer; Carla M. D’Antonio; Jennifer Y. King (Oecologia, 2016)

An 850‐year tree‐ring‐based reconstruction of drought history in the western Qilian Mountains of northwestern China - Xiaohua Gou; Linlin Gao; Yang Deng; Fahu Chen; Meixue Yang; Christopher Still (International Journal of Climatology, 2015)
Studies of regional drought history will be helpful for understanding current hydroclimate variability with global warming as well as predicting future hydroclimate shifts. Long‐term tree‐ring records are scarce in the western Qilian Mountains of northwestern China, which is also the western boundary of the natural distribution of Qilian Juniper ( Juniperus przewalskii Kom.) in this area. Here, we present an 850‐year ( AD 1161 –2010) reconstruction of May–July self‐calibrating Palmer Drought Severity Index ( scPDSI ) in the western Qilian Mountains that is based on two nearly millennia of ring‐width chronologies derived from long‐lived Qilian Juniper trees. The reconstruction suggests a relatively dry phase from the 15th century to the 18th century during the Little Ice Age ( LIA ) and a relatively wet period over the past two centuries. This reconstruction is consistent with other tree‐ring‐based hydroclimatic reconstructions from the northeastern Tibetan Plateau, as well as the corresponding century‐scale solar activity during the LIA . The three mega‐drought periods ( AD 1260s –1340s, 1430s–1540s and 1640s–1740s) recorded by the tree‐ring series also correspond to the Wolf, Spörer and Maunder solar activity minimum periods. Results of the multi‐tape method analysis and wavelet analysis further confirmed the relationship between regional hydroclimate variability and solar activity forcing.

Biogeographically distinct controls on C 3 and C 4 grass distributions: merging community and physiological ecology - Daniel M. Griffith; T. Michael Anderson; Colin P. Osborne; Caroline A. E. Strömberg; Elisabeth J. Forrestel; Christopher J. Still (Global Ecology and Biogeography, 2015)
Aim C 4 photosynthesis is an adaptation that maintains efficient carbon assimilation in high‐light, high‐temperature conditions. Due to the importance of C 4 grasses for carbon and surface energy fluxes, numerous models have been proposed to describe their spatial distribution and forecast their responses to climate change. These models often rely on broad climatic predictors (e.g. temperature and precipitation) but fail to integrate other ecologically relevant factors like disturbance and competition, which may modify realized C 3 / C 4 grass distributions. Here, we present a combined evaluation of the contribution of ecological factors and climatic predictors to realized C 3 / C 4 grass distributions. We consider multiple biogeographic regions of N orth A merica using a multisource database of over 40,000 vegetation plots. Location The conterminous U nited S tates of A merica ( USA ). Methods We identified a comprehensive pool of climatic models in the literature and used information theoretic criteria to select a primary climatic predictor of C 3 and C 4 grass distributions. Subsequently, the best model was combined with ecological predictors (e.g. fire, tree cover) using a multiple regression framework and tested within eight regions. Results Surprisingly, grass‐dominated communities across the USA exist largely in C 3 ‐ or C 4 ‐dominated states. Transitions between C 3 / C 4 dominance were best explained by models that integrated temperature and precipitation with ecological factors that varied according to region. For some regions, like E astern T emperate F orests, local ecological factors were comparable in strength to broad‐scale climatic predictors of C 3 / C 4 abundance. Main conclusion Local ecological factors modify C 3 / C 4 grass responses to broad‐scale climatic drivers in ways that manifest at regional scales. In E astern T emperate F orests, for example, C 4 grass abundances are maintained below climatic expectations where tree cover creates light limitation but above expectations where frequent fires reduce tree cover. Thus, local ecological factors, which vary among biogeographic regions, contribute to large‐scale climate disequilibrium.

Land surface skin temperature captures thermal environments of C 3 and C 4 grasses - Christopher J. Still; Stephanie Pau; Erika J. Edwards (Global Ecology and Biogeography, 2014)
Aim Numerous studies have documented ecological sorting of C 3 and C 4 grasses along air temperature gradients. However, phylogenetically structured analyses suggest that closely related C 3 and C 4 grasses (in the same PACMAD clade: P anicoideae, A rundinoideae, C hloridoideae, M icrairoideae, A ristidoideae and D anthonioideae) occur in environments with similar air temperature, challenging our understanding of how the photosynthetic pathway influences grass biogeography. To better understand thermal differences between C 3 and C 4 grass lineages, we analysed the surface radiative temperature as an alternative measure that is more closely aligned with plant microclimate. Location H awaiian I slands, USA . Methods We used the MODIS land surface temperature ( LST ) product, a satellite‐based measurement of radiative temperature. We compared LST with mean annual air temperature ( MAT ) for locations where C 3 and C 4 grass species were collected. We also utilized other satellite products, like MODIS tree cover, as a proxy for relative habitat openness where these grasses occur. Results Comparisons of C 3 lineages [in BEP ( B ambusoideae, E hrhartoideae and P ooideae) and PACMAD clades] and C 4 lineages ( PACMAD clade only) illustrate the differing thermal environments for each group. C 4 taxa are found in the environments with the highest MAT , followed by C 3 PACMAD species. By contrast, C 3 PACMAD species are found in the environments with the coolest LST , and the LST values for C 3 BEP species are substantially higher than their MAT values. The difference in LST between C 3 and C 4 PACMADs is larger than the difference in MAT between these groups. Main conclusions Though LST has been used infrequently in ecology and biogeography, it is intimately related to water and energy balance and ecosystem structure, and should more accurately capture plant temperatures and microclimates than MAT . Our results provide support for a pronounced thermal difference in the environments of closely related C 3 and C 4 grass taxa, and show that C 3 PACMADs occur in the coolest and least variable thermal environments, probably due to the greater tree cover of these habitats.

Cloud shading and fog drip influence the metabolism of a coastal pine ecosystem - Mariah S. Carbone; A. Park Williams; Anthony R. Ambrose; Claudia M. Boot; Eliza S. Bradley; Todd E. Dawson; Sean M. Schaeffer; Joshua P. Schimel; Christopher J. Still (Global Change Biology, 2013)
Assessing the ecological importance of clouds has substantial implications for our basic understanding of ecosystems and for predicting how they will respond to a changing climate. This study was conducted in a coastal Bishop pine forest ecosystem that experiences regular cycles of stratus cloud cover and inundation in summer. Our objective was to understand how these clouds impact ecosystem metabolism by contrasting two sites along a gradient of summer stratus cover. The site that was under cloud cover ~15% more of the summer daytime hours had lower air temperatures and evaporation rates, higher soil moisture content, and received more frequent fog drip inputs than the site with less cloud cover. These cloud‐driven differences in environmental conditions translated into large differences in plant and microbial activity. Pine trees at the site with greater cloud cover exhibited less water stress in summer, larger basal area growth , and greater rates of sap velocity. The difference in basal area growth between the two sites was largely due to summer growth. Microbial metabolism was highly responsive to fog drip, illustrated by an observed ~3‐fold increase in microbial biomass C with increasing summer fog drip. In addition, the site with more cloud cover had greater total soil respiration and a larger fractional contribution from heterotrophic sources. We conclude that clouds are important to the ecological functioning of these coastal forests, providing summer shading and cooling that relieve pine and microbial drought stress as well as regular moisture inputs that elevate plant and microbial metabolism. These findings are important for understanding how these and other seasonally dry coastal ecosystems will respond to predicted changes in stratus cover, rainfall, and temperature.

Improving our understanding of environmental controls on the distribution of C 3 and C 4 grasses - Stephanie Pau; Erika J. Edwards; Christopher J. Still (Global Change Biology, 2013)
A number of studies have demonstrated the ecological sorting of C 3 and C 4 grasses along temperature and moisture gradients. However, previous studies of C 3 and C 4 grass biogeography have often inadvertently compared species in different and relatively unrelated lineages, which are associated with different environmental settings and distinct adaptive traits. Such confounded comparisons of C 3 and C 4 grasses may bias our understanding of ecological sorting imposed strictly by photosynthetic pathway. Here, we used MaxEnt species distribution modeling in combination with satellite data to understand the functional diversity of C 3 and C 4 grasses by comparing both large clades and closely related sister taxa. Similar to previous work, we found that C 4 grasses showed a preference for regions with higher temperatures and lower precipitation compared with grasses using the C 3 pathway. However, air temperature differences were smaller (2 °C vs. 4 °C) and precipitation and % tree cover differences were larger (1783 mm vs. 755 mm, 21.3% vs. 7.7%, respectively) when comparing C 3 and C 4 grasses within the same clade vs. comparing all C 4 and all C 3 grasses (i.e., ignoring phylogenetic structure). These results were due to important differences in the environmental preferences of C 3 BEP and PACMAD clades (the two main grass clades). Winter precipitation was found to be more important for understanding the distribution and environmental niche of C 3 PACMAD s in comparison with both C 3 BEP s and C 4 taxa, for which temperature was much more important. Results comparing closely related C 3 –C 4 sister taxa supported the patterns derived from our modeling of the larger clade groupings. Our findings, which are novel in comparing the distribution and niches of clades, demonstrate that the evolutionary history of taxa is important for understanding the functional diversity of C 3 and C 4 grasses, and should have implications for how grasslands will respond to global change.

Seasonal and episodic moisture controls on plant and microbial contributions to soil respiration - Mariah S. Carbone; Christopher J. Still; Anthony R. Ambrose; Todd E. Dawson; A. Park Williams; Claudia M. Boot; Sean M. Schaeffer; Joshua P. Schimel (Oecologia, 2011)

Significance of summer fog and overcast for drought stress and ecological functioning of coastal California endemic plant species - Douglas T. Fischer; Christopher J. Still; A. Park Williams (Journal of Biogeography, 2009)
Aim Fog drip is a crucial water source for plants in many ecosystems, including a number of global biodiversity hotspots. In California, dozens of rare, drought‐sensitive plant species are endemic to coastal areas where the dominant summer moisture source is fog. Low clouds that provide water to these semi‐arid ecosystems through fog drip can also sharply reduce evaporative water losses by providing shade. We quantified the relative hydrological importance of cloud shading vs. fog drip. We then examined how both factors influence the range dynamics of an apparently fog‐dependent plant species spanning a small‐scale cloud gradient. Location The study area is on Santa Cruz Island off the coast of southern California. It is near the southern range limit of bishop pine ( Pinus muricata D. Don), a tree endemic to the coasts of California and Baja, Mexico. Methods We measured climate across a pine stand along a 7 km, coastal–inland elevation transect. Short‐term (1–5 years) monitoring and remote sensing data revealed strong climatic gradients driven primarily by cloud cover. Long‐term (102 years) effects of these gradients were estimated using a water balance model. Results We found that shade from persistent low clouds near the coast reduced annual drought stress by 22–40% compared with clearer conditions further inland. Fog drip at higher elevations provided sufficient extra water to reduce annual drought stress by 20–36%. Sites located at both high elevation and nearer the coast were subject to both effects. Together, these effects reduced average annual drought stress by 56% and dramatically reduced the frequency of severe drought over the last century. At lower elevation (without appreciable fog drip) and also near the inland edge of the stand (with less cloud shading) severe droughts episodically kill most pine recruits, thereby limiting the local range of this species. Main conclusions Persistent cloud shading can influence hydrology as much as fog drip in cloud‐affected ecosystems. Understanding the patterns of both cloud shading and fog drip and their respective impacts on ecosystem water budgets is necessary to fully understand past species range shifts and to anticipate future climate change‐induced range shifts in fog‐dependent ecosystems.

The influence of summertime fog and overcast clouds on the growth of a coastal Californian pine: a tree-ring study - A. Park Williams; Christopher J. Still; Douglas T. Fischer; Steven W. Leavitt (Oecologia, 2008)

Climate, phylogeny and the ecological distribution of C4 grasses - Erika J. Edwards; Christopher J. Still (Ecology Letters, 2008)
‘C4 photosynthesis’ refers to a suite of traits that increase photosynthesis in high light and high temperature environments. Most C4 plants are grasses, which dominate tropical and subtropical grasslands and savannas but are conspicuously absent from cold growing season climates. Physiological attributes of C4 photosynthesis have been invoked to explain C4 grass biogeography; however, the pathway evolved exclusively in grass lineages of tropical origin, suggesting that the prevalence of C4 grasses in warm climates could be due to other traits inherited from their non‐C4 ancestors. Here we investigate the relative influences of phylogeny and photosynthetic pathway in determining the ecological distributions of C4 grasses in Hawaii. We find that the restriction of C4 grasses to warmer areas is due largely to their evolutionary history as members of a warm‐climate grass clade, but that the pathway does appear to confer a competitive advantage to grasses in more arid environments.

Large‐scale plant light‐use efficiency inferred from the seasonal cycle of atmospheric CO 2 - Christopher J. Still; James T. Randerson; Inez Y. Fung (Global Change Biology, 2004)
We combined atmospheric CO 2 measurements, satellite observations, and an atmospheric transport model in an inverse modeling framework to infer a key property of vegetation physiology, the light‐use efficiency (LUE) of net primary production, for large geographic regions. We find the highest LUE in boreal regions and in the northern hemisphere tropics. Within boreal zones, Eurasian LUE is higher than North American LUE and has a distinctly different seasonal profile. This longitudinal asymmetry is consistent with ecological differences expected from the much greater cover of deciduous vegetation in boreal Eurasia caused by the vast Siberian forests of the deciduous conifer, Larch. Inferred LUE of the northern hemisphere tropics is also high and displays a seasonal profile consistent with variations of both cloud cover and C 4 vegetation activity.

18 O composition of CO 2 and H 2 O ecosystem pools and fluxes in a tallgrass prairie: Simulations and comparisons to measurements - William J. Riley; Christopher J. Still; Brent R. Helliker; Miguel Ribas‐Carbo; Joseph A. Berry (Global Change Biology, 2003)
In this paper we describe measurements and modeling of 18 O in CO 2 and H 2 O pools and fluxes at a tallgrass prairie site in Oklahoma. We present measurements of the δ 18 O value of leaf water, depth‐resolved soil water, atmospheric water vapor, and Keeling plot δ 18 O intercepts for net soil‐surface CO 2 and ecosystem CO 2 and H 2 O fluxes during three periods of the 2000 growing season. Daytime discrimination against C 18 OO, as calculated from measured above‐canopy CO 2 and δ 18 O gradients, is also presented. To interpret the isotope measurements, we applied an integrated land‐surface and isotope model (ISOLSM) that simulates ecosystem H 2 18 O and C 18 OO stocks and fluxes. ISOLSM accurately predicted the measured isotopic composition of ecosystem water pools and the δ 18 O value of net ecosystem CO 2 and H 2 O fluxes. Simulations indicate that incomplete equilibration between CO 2 and H 2 O within C 4 plant leaves can have a substantial impact on ecosystem discrimination. Diurnal variations in the δ 18 O value of above‐canopy vapor had a small impact on the predicted δ 18 O value of ecosystem water pools, although sustained differences had a large impact. Diurnal variations in the δ 18 O value of above‐canopy CO 2 substantially affected the predicted ecosystem discrimination. Leaves dominate the ecosystem 18 O‐isoflux in CO 2 during the growing season, while the soil contribution is relatively small and less variable. However, interpreting daytime measurements of ecosystem C 18 OO fluxes requires accurate predictions of both soil and leaf 18 O‐isofluxes.

The contribution of C 3 and C 4 plants to the carbon cycle of a tallgrass prairie: an isotopic approach - Christopher J. Still; Joseph A. Berry; Miquel Ribas-Carbo; Brent R. Helliker (Oecologia, 2003)